2015
DOI: 10.1063/1.4922616
|View full text |Cite
|
Sign up to set email alerts
|

Accurate ab initio potential energy surface, thermochemistry, and dynamics of the F− + CH3F SN2 and proton-abstraction reactions

Abstract: Articles you may be interested inWe develop a full-dimensional global analytical potential energy surface (PES) for the F − + CH 3 F reaction by fitting about 50 000 energy points obtained by an explicitly correlated composite method based on the second-order Møller-Plesset perturbation-F12 and coupled-cluster singles, doubles, and perturbative triples-F12a methods and the cc-pVnZ-F12 [n = D, T] basis sets. The PES accurately describes the (a) back-side attack Walden inversion mechanism involving the pre-and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(80 citation statements)
references
References 41 publications
3
76
0
1
Order By: Relevance
“…However, we found that one cannot distinguish between the two mechanisms based on simply the integration time, as we did in the case of the F – + CH 3 Cl, F – + CH 3 F, and F – + CHD 2 Cl reactions. 6,35,36 Fig. 3 also shows the cross sections for the induced inversions of the CH 3 I reactant, which are not followed by a substitution resulting in an inverted reactant.…”
Section: Resultsmentioning
confidence: 99%
“…However, we found that one cannot distinguish between the two mechanisms based on simply the integration time, as we did in the case of the F – + CH 3 Cl, F – + CH 3 F, and F – + CHD 2 Cl reactions. 6,35,36 Fig. 3 also shows the cross sections for the induced inversions of the CH 3 I reactant, which are not followed by a substitution resulting in an inverted reactant.…”
Section: Resultsmentioning
confidence: 99%
“…The noncovalent index (NCI) was also used to illustrate this S N 2 reaction in solution . S N 2 reactions in systems with different incoming and outgoing halogen atoms, and alternative mechanisms (front‐side attack, double inversion, and hydrogen abstraction) have also been investigated …”
Section: Introductionmentioning
confidence: 99%
“… 14 , 23 Also a hydrogen-bonded prereaction complex where the anion points to a C–H bond axis of the methyl halide has been established. 24 , 25 These alternative entrance channel geometries not only change the kinematics and dynamics of the reaction producing the mechanisms mentioned above but also can lead to completely different products competing with nucleophilic substitution in these ion–molecule reactive systems, e.g. : Reaction ( 2 ) consists of a proton abstraction mechanism induced by an XH-bonded prereaction complex, whereas reaction ( 3 ) produces a dihalide anion through a halogen abstraction mechanism.…”
Section: Introductionmentioning
confidence: 99%
“… 28 , 29 Theoretical studies have focused mainly on the reaction type ( 2 ), investigating the properties of the [X–HCH 2 Y] − prereaction complex. 24 , 25 , 30 The contribution of the proton transfer channel has been shown to strongly depend on the proton affinity of the nucleophile. 21 The halogen abstraction mechanism, which produces a dihalide anion, has only seen little attention up to now.…”
Section: Introductionmentioning
confidence: 99%